2012
DOI: 10.1002/gps.3802
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neopterin level as a marker of peripheral immune activation in amnestic mild cognitive impairment and Alzheimer's disease

Abstract: Objective Alterations of the immune system play important roles in Alzheimer’s disease (AD). The primary purpose of this study was to compare plasma levels of neopterin, a marker of cellular immune activity, in amnestic Mild Cognitive Impairment (aMCI), early (mild to moderate) AD, and cognitively normal controls (NC). In addition, correlation of plasma neopterin with interferon-gamma (INF-γ) and Interleukin-6 (IL-6) were also examined. Methods Plasma samples from patients with mild to moderate AD (N=35), aM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…However, and disappointingly, administration of nonsteroidal anti-inflammatory agents had no effect on the progression of established AD in several clinical trials [24], raising the interest in the exploitation of other mechanisms involved in the pathogenesis of the disease, among which is the immune system. An increasing number of studies have reported changes in immune system activity, namely, alterations in lymphocyte and macrophage distribution and activation, production of antibodies against self-proteins, as well as atypical proinflammatory factors [25][26][27]. A recent study showed that the pathogenesis of AD in APPSwDI(+)/(+)mNos2(−/−)(CVN)-AD mice is driven by local immune suppression as areas of hippocampal neuronal death are associated with the presence of immunosuppressive CD11c + microglia and extracellular arginase, resulting in arginine catabolism and reduced levels of total brain arginine [28].…”
Section: Pathogenesis Of Alzheimer's Diseasementioning
confidence: 99%
“…However, and disappointingly, administration of nonsteroidal anti-inflammatory agents had no effect on the progression of established AD in several clinical trials [24], raising the interest in the exploitation of other mechanisms involved in the pathogenesis of the disease, among which is the immune system. An increasing number of studies have reported changes in immune system activity, namely, alterations in lymphocyte and macrophage distribution and activation, production of antibodies against self-proteins, as well as atypical proinflammatory factors [25][26][27]. A recent study showed that the pathogenesis of AD in APPSwDI(+)/(+)mNos2(−/−)(CVN)-AD mice is driven by local immune suppression as areas of hippocampal neuronal death are associated with the presence of immunosuppressive CD11c + microglia and extracellular arginase, resulting in arginine catabolism and reduced levels of total brain arginine [28].…”
Section: Pathogenesis Of Alzheimer's Diseasementioning
confidence: 99%
“…Neopterin is a marker of peripheral immune system activation [9]. Increased neopterin concentrations in body fluids of patients are observed during diseases with activated cellular (=TH1-type) immune response such as allograft rejection, virus infections [10], autoimmune disorders, or malignant tumors [11] but also in neurodegenerative diseases or during pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%
“…In AD, brains are characterized by the presence of neurofibrillary tangles, prominent activation of a local inflammatory response and accumulation of β-amyloid into amyloid plaques. Apart from brain-specific changes, an increasing number of studies in AD have reported alterations in systemic immune responses including changes in lymphocyte and macrophage distribution and activation, the presence of autoantibodies, or abnormal inflammatory factors and cytokine production (Kusdra et al, 2000, Galimberti et al, 2006, Mruthinti et al, 2006, Speciale et al, 2007, Pellicano et al, 2010, Hochstrasser et al, 2011, Kim et al, 2011, Parker et al, 2013, Pellicano et al, 2012). Earlier studies on blood specimens from patients with AD also found elevated levels of plasma lipopolysaccharide (LPS), a potent inflammatory stimulus, and the degree of this elevation was directly related to levels of abnormally activated blood monocyte/macrophages (MO) in AD patients (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%